Seroprevalence Of Cytomegalovirus Among Hemodialysis Patients In Misurata City-Libya (Journal of Medical Sciences, 2020)
Cytomegalovirus (CMV) belongs to the herpes virus family, it has the ability to cause systemic infection and serious diseases in immunocompromised patients such as hemodialysis patients. The aim of this study was to investigate the prevalence of CMV infection among hemodialysis (HD)  patients. One hundred and seventy (170) of HD patients (95 males & 75 females) attending the Misurata center for nephrology and dialysis were included in this cross-sectional study, thirty (30) of apparently healthy individuals (13 male & 17 female) were also employed as a control group. Detection of CMV-IgM & CMV-IgG antibodies in serum samples was carried out by Enzyme-Linked Immunosorbent Assay technique. Results showed that CMV-IgM antibodies were detected in 29/200 (14.5%) of the total study population, whereas 21/170 (12.4%) of hemodialysis patients  and 8/30 (26.7%) of control subjects were seropositive for CMV IgM antibodies; in addition  186/200 (93%) of the total study population were seropositive for CMV-IgG antibodies, in which 162/170 (95.3%) of HD patients and  24/30 (80%) of the control group were seropositive for CMV IgG antibodies; the seroprevalence of CMV-IgM antibodies was significantly correlated with the frequency of hemodialysis/week, kidney transplantation, blood transfusion, surgical operations, and therapeutic drugs (P= 0.035, 0.039, 0.041, 0.000, and 0.004 respectively); however, seroprevalence of CMV-IgG antibodies was significantly associated with duration of ESRD & HD, and frequency of hemodialysis/week (P= 0.019, 0.020 respectively). In conclusion, results showed a high prevalence of CMV infection among the study population, which could be related to duration of ESRD & HD, blood transfusion, frequency of hemodialysis/week, surgical operations, therapeutic drugs.